Giống đậu tương ngắn ngày DT99 và ứng dụng trong các hệ thống canh tác tiến bộ - Mai, Quang Vinh (2011)
Tác giả: Mai Quang Vinh, PGS.TS; Mai Quang Vinh, PGS.TS; Ngô Phương Thịnh, CN; Trần Thuý Oanh, KS -- Từ khóa: Đậu tương